2001
DOI: 10.1111/1467-9914.00173
|View full text |Cite
|
Sign up to set email alerts
|

International Migration Dynamics: The Role of Experience and Social Networks

Abstract: This paper tests the dynamic implications of cumulative causation and network theory on the self-sustaining nature of the migration process. A sequential migration model is derived and estimated with a panel of Mexican household heads for the years 1980± 89. Consistently with cumulative causation and network theory, the empirical results show that, after controlling for unobserved heterogeneity, previous migration experience and migration-related variables are the strongest predictors of current migration deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 16 publications
4
32
0
7
Order By: Relevance
“…The hypothesis is that the propensity of people to migrate from one place is also a function of the amount of people from that place who have previously migrated (Greenwood, 1969(Greenwood, , 1972, the reason being that information flows from former migrants encourage current migration. This argument is also consistent with the key role exerted by social networks in reducing the risks and the costs of migration (Deléchat, 2001;Zhao, 1993): migrant network may supply to potential migrants a great range of information and advice on job opportunities, may lower psychological costs by offering emotional support to migrants in the new residence area, and may grant migrants initial housing and logistic support. A number of studies have shown the positive effect exerted by migrant networks on migration (see, for instance, Massey et al, 1993;Banerjee, 1984).…”
Section: The Modelsupporting
confidence: 68%
“…The hypothesis is that the propensity of people to migrate from one place is also a function of the amount of people from that place who have previously migrated (Greenwood, 1969(Greenwood, , 1972, the reason being that information flows from former migrants encourage current migration. This argument is also consistent with the key role exerted by social networks in reducing the risks and the costs of migration (Deléchat, 2001;Zhao, 1993): migrant network may supply to potential migrants a great range of information and advice on job opportunities, may lower psychological costs by offering emotional support to migrants in the new residence area, and may grant migrants initial housing and logistic support. A number of studies have shown the positive effect exerted by migrant networks on migration (see, for instance, Massey et al, 1993;Banerjee, 1984).…”
Section: The Modelsupporting
confidence: 68%
“…Wahba (2001Wahba ( , 2003 and Wahba and Zenou (2012) for Egypt. Another valuable source of retrospective migration histories is the Mexican Migration Project (MMP), which has been widely used in both the sociological (e.g., Massey, Durand, and Malone, 2002;Gentsch and Massey, 2014) and economic literature (e.g., Deléchat, 2001;Colussi, 2003;Rendon and Cuecuecha, 2010;Thom, 2010;Angelucci, 2012;Lessem, 2013;Reinhold andThom, 2013, Nakajima, 2014a,b (Brücker et al, 2014).…”
Section: Migration Temporariness: Data and Measurementmentioning
confidence: 99%
“…There are few similar models developed elsewhere (e.g., Deléchat, 2001;Colussi, 2003;Bellemare, 2007;van Baalen and Müller, 2008;Thom, 2010;Rendon and Cuecuecha, 2010;Kırdar, 2012;Lessem, 2013;Nakajima, 2014a,b) that address aspects of temporary migration. Using this model, we first identify and graphically simulate the possible triggers of temporary migration and then, while referencing pertinent studies, develop the implications of return plans for some economic behaviors, including human capital investment, labor supply, and savings.…”
Section: Modeling Temporary Migrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the literature has evolved to analyze migration using dynamics models that allow for bidirectional migration over the life cycle. Interestingly, most of these models focus their attention in the formation and impact of social networks formed by migrants (Delechat 2001, Angelucci 2002, Haslag, Guzman and Orrenious 2004, Colussi 2006, Kennan and Walker 2006, Gemici 2007). …”
Section: Introductionmentioning
confidence: 99%